سبب نزول کی عبارات کے صیغے ؛ علامہ الطیار کے استدلالات کا تجزیاتی مطالعہ: Phraseologies in Circumstances of Revelation; Analytical Study of Allama al-Tayyār’s Inferences - Rabiya Zaheer*; Dr.Muhammad Farooq Haider (jihat-ul-islam, 2023)
One of the most important aspects of Circumstances of Revelation are the phraseologies that appeared in the traditions related to the aforementioned subject. In this regard, difference of opinions exists between the predecessors and the later ones. These phraseologies are used with respect to both perspectives i.e for narrating the explicit occasion of revelation and for exegetical purposes as well. Due to their vast and extensive implementation differences occurred in the exegetical interpretations and sometimes multiple occasion of revelation are quoted under the same verse. Although there is no source in this context that can be referred to as an authority in order to settle the disagreement but after having a detail analysis of the whole matter, it can be inferred that most of the traditions indicate the use of phraseology "Fa anzal Allah, Fanazalat" for explicitly narrating the cause of revelation whereas phraseology "Nazalat fi kaza, Unzilat fi kaza" is mostly used in terms of interpretation. These terminologies remained a constant subject of discussion in the books of Quranic sciences. This article aims at studying the findings of modern researcher Allama Musā’id al-Tayyar in this regard.